2003
DOI: 10.1111/1468-0262.00418
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Forecasting Realized Volatility

Abstract: This paper provides a general framework for integration of high-frequency intraday data into the measurement, modeling, and forecasting of daily and lower frequency volatility and return distributions. Most procedures for modeling and forecasting financial asset return volatilities, correlations, and distributions rely on restrictive and complicated parametric multivariate ARCH or stochastic volatility models, which often perform poorly at intraday frequencies. Use of realized volatility constructed from high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
690
1
12

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,984 publications
(794 citation statements)
references
References 101 publications
13
690
1
12
Order By: Relevance
“…dollar exchange rate, i.e., the number of Yen per U.S. dollar. In order to avoid modeling particular weekend effects, we exclude all of the observations on Saturdays and Sundays (Andersen et al, 2003). Consequently, our full sample includes the daily average Yen/U.S.…”
Section: Case Studymentioning
confidence: 99%
“…dollar exchange rate, i.e., the number of Yen per U.S. dollar. In order to avoid modeling particular weekend effects, we exclude all of the observations on Saturdays and Sundays (Andersen et al, 2003). Consequently, our full sample includes the daily average Yen/U.S.…”
Section: Case Studymentioning
confidence: 99%
“…The paper uses three approaches to evaluate stock market comovement in the daily returns of European stock exchanges: (1) Following Andersen, et al (2003), the authors define daily returns as …”
Section: Empirical Approachmentioning
confidence: 99%
“…Of particular relevance is Diebold and Inoue (2001) who showed that a process with Markov switching regimes can be mistaken for a long memory process; so that long memory can arise from some forms of nonlinearity. A priori it would seem reasonable for the long memory property found in macroeconomic series such as in ‡ation to be due to regime shifts in monetary policy; while realized volatility in frictionless …nancial markets seem to be pure long memory; Andersen, Bollerslev, Diebold and Labys (2003). However, the application of the tests developed by Baillie and Kapetanios (2007) suggested the existence of both nonlinear and long memory components in many economic and …nancial time series.…”
Section: Nonlinear-long Memory Modelsmentioning
confidence: 99%